Climate Policy 2016
DOI: 10.1201/b20720-8
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development and Technological Impact on CO2 Reducing Conditions in Romania

Abstract: Ozone and methane are chemically active climate-forcing agents affected by climate-chemistry interactions in the atmosphere. Key chemical reactions and processes affecting ozone and methane are presented. It is shown that climate-chemistry interactions have a significant impact on the two compounds. Ozone, which is a secondary compound in the atmosphere, produced and broken down mainly in the troposphere and stratosphre through chemical reactions involving atomic oxygen (O), NOx compounds (NO, NO 2 ), CO, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…With a lifetime of approximately a decade in the atmosphere, methane is well mixed globally and therefore has a significant influence on background ozone levels. Methane is a distinct win-win possibility for air quality and climate in that reductions in methane emissions would decrease ozone, including baseline ozone, and thereby lessen adverse impacts on vegetation and human health, but also benefit climate by reducing two greenhouse gases simultaneously (Fry et al, 2012;Shindell et al, 2012;Isaksen et al, 2014). A model study investigated the air quality (O 3 ) and climate benefits of methane reductions and found that O 3 reductions were relatively linear with respect to reduc- Figure 43.…”
Section: The Future -Air Quality and Climatementioning
confidence: 99%
“…With a lifetime of approximately a decade in the atmosphere, methane is well mixed globally and therefore has a significant influence on background ozone levels. Methane is a distinct win-win possibility for air quality and climate in that reductions in methane emissions would decrease ozone, including baseline ozone, and thereby lessen adverse impacts on vegetation and human health, but also benefit climate by reducing two greenhouse gases simultaneously (Fry et al, 2012;Shindell et al, 2012;Isaksen et al, 2014). A model study investigated the air quality (O 3 ) and climate benefits of methane reductions and found that O 3 reductions were relatively linear with respect to reduc- Figure 43.…”
Section: The Future -Air Quality and Climatementioning
confidence: 99%
“…With a lifetime of approximately a decade in the atmosphere, methane is well mixed globally and therefore has a significant influence on background ozone levels. Methane is a distinct win-win possibility for air quality and climate in that reductions in methane emissions would decrease ozone, including baseline ozone, and thereby lessen adverse impacts on vegetation and human health, but also benefit climate by reducing two greenhouse gases simultaneously (Fry et al, 2012;Shindell et al, 2012;Isaksen et al, 2014). A model study investigated the air quality (O 3 ) and climate benefits of methane reductions and found that O 3 reductions were relatively linear with respect to reduc- Figure 43.…”
Section: The Future -Air Quality and Climatementioning
confidence: 99%
“…Increasing atmospheric CH 4 would accelerate near-S. B. Dalsøren et al: Atmospheric methane evolution the last 40 years term warming, due to its strong climate impact on a 20-year time frame (Myhre et al, 2013). Enhanced CH 4 levels would also increase the ozone levels in surface air (Fiore et al, 2008(Fiore et al, , 2012West and Fiore, 2005;Isaksen et al, 2014), and thereby worsen air pollution impacts on vegetation, crops, and human health.…”
Section: Introductionmentioning
confidence: 99%